Persepsi Siswa Kelas XI Terhadap Pengelolaan Kegiatan Ekstrakurikuler Kepramukaan Di SMK Negeri - Lola Yolanda; Nelfia Adi; Hanif Al Kadri; Anisah Anisah (Universitas Negeri Padang, 2021)
This research is a quantitative descriptive study, with the aim of obtaining information about the Perceptions of Class XI Students on the Management of Scouting Extracurricular Activities at SMK state. The population of this research is all class XI totaling 469 students, the technique used is Proportional Random Sampling with a sample of 87 students. The instrument used was a questionnaire in the form of a Likert scale. The results showed that 1) the students' perceptions seen from the planning aspect of scouting extracurricular activities were in the good category with a score of 4.00; 2) Students' perceptions seen from the organizational aspect were categorized as good with a score of 4.01; 3) Judging from the aspect of scouting extracurricular activities in the good category with a score of 3.83; 4) and student perceptions seen from the aspect of supervision are in the good category with a score of 4.05. So it can be concluded that students' perceptions of the management of scouting extracurricular activities at SMK state were classified as good with a score of 3.97.